Dansk nytestamentlig forskning i 1980’erne - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1991)
This survey is an attempt to contribute to a much needed discussion of how to improve the quality of Danish New Testament research with the overall aim to make it more attractive to a wider circle of educated Danish readers. In other words, this survey is meant as an attempt to call Danish New Testament scholars to a self-critical discussion of the ways and lines Danish New Testament research has taken in the 1980s wehre, in my opinion, it has lost some of its earlier contact with both the academics and the general Danish public. In the article, Danish New Testament scholarship in the 1980s (and, to some extent, also in the 1970s and 1960s) is surveyed and examined critically. the "medicine" which is suggested to "cure the disease" is - to a greater extent, and by using the results of other related disciplines - to place the various examinations and interpretations of the New Testament and christian beginnings in wider historical and cultural contexts.